Ecological resilience in a changing world: Challenges and opportunities in biodiversity conservation in the face of climate change - Dias, Reinaldo (Seven Editora, 2023)
This chapter investigates the impacts of climate change on biodiversity and explores the conservation and adaptation strategies needed to address this global threat. Through a systematic review of the scientific literature, the study analyzes the effects of climate change at different geographical and taxonomic scales, identifying trends, patterns, and gaps in current knowledge. In addition, the adaptive responses of species and ecosystems and the implications for biodiversity conservation are discussed. Finally, the chapter presents an assessment of the most effective conservation and adaptation strategies, including in situ and ex situ measures, ecological restoration, and international policies. The aim is to contribute to the debate on the management of natural resources in the context of climate change and to guide decision-making in relation to biodiversity conservation and adaptation to climate change. DOI:https://doi.org/10.56238/alookdevelopv1-176